2001
DOI: 10.1111/j.1348-0421.2001.tb01325.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mumps Virus Isolated in Saitama Prefecture, Japan, by Sequence Analysis of the SH Gene

Abstract: Mumps virus (MuV) strains isolated from cerebrospinal fluid and throat swabs from patients in Saitama Prefecture and Tokyo, Japan, from 1997 to 2000 were examined by analyzing the SH gene nucleotide sequence (316-nt). Eighteen of the 20 strains studied were divided into three genotypes, recognized as B, G, and H in previous reports. Two genotypes (G and H) are believed to be new in Japan. Two of the 20 strains belonged to none of the previously reported genotypes (A-I), but were closely related to two known st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
30
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 14 publications
3
30
0
Order By: Relevance
“…The phylogenetic relation based on the F gene of other genotypes is not yet clear. On the other hand, we have reported the first isolation of MuV strains of 3 different genotypes in Japan during a recent mumps epidemic and outbreaks in Saitama Prefecture; genotype G was found in 1999 and 2000, H was found in 1997, and J which we proposed as a new genotype was found in 1997 and 1999 (23). Those results suggested that the mumps epidemic in the year 2000 was caused by genotype G strains (23).…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…The phylogenetic relation based on the F gene of other genotypes is not yet clear. On the other hand, we have reported the first isolation of MuV strains of 3 different genotypes in Japan during a recent mumps epidemic and outbreaks in Saitama Prefecture; genotype G was found in 1999 and 2000, H was found in 1997, and J which we proposed as a new genotype was found in 1997 and 1999 (23). Those results suggested that the mumps epidemic in the year 2000 was caused by genotype G strains (23).…”
mentioning
confidence: 68%
“…One purpose of this study is to investigate MuV genotypes circulating in the prefecture since 2000, and to provide better characterization of the F gene of strains isolated in recent years in Japan. Another purpose is to confirm that the genotype proposed as J in our previous study (23) is different from genotype J designated by Tecle et al (21), and to rename the genotype we found to eliminate confusion. First, in the present study, we analyzed the SH gene of MuV strains isolated in Saitama Prefecture from 1997 to 2001 and other reported strains including genotype J identified by Tecle et al Then, we compared the phylogenetic analyses of the F gene among different genotypes and the alignments of deduced amino acid sequences obtained in this study to previously reported strains, especially those isolated in Japan.…”
mentioning
confidence: 87%
See 3 more Smart Citations